2014
DOI: 10.5005/jsafog-6-2-129
|View full text |Cite
|
Sign up to set email alerts
|

Review: Fetal Programming of Polycystic Ovary Syndrome by Androgen Excess — Evidence from Experimental, Clinical and Genetic Association Studies

Abstract: ObjectivePolycystic ovary syndrome (PCOS) is a common endocrine disorder of premenopausal women, characterized by hyperandrogenism, polycystic ovaries, and chronic anovulation along with insulin resistance and abdominal obesity as frequent metabolic traits. Although, PCOS manifests clinically during adolescence, emerging data suggest that the natural history of PCOS may originate in intrauterine life. Evidence AcquisitionEvidence from experimental, clinical, and genetic research supporting the hypothesis for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
43
0
4

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(48 citation statements)
references
References 0 publications
1
43
0
4
Order By: Relevance
“…Different animal models have demonstrated that experimentally induced prenatal androgen excess in female fetuses results in changes that, in adulthood, resemble those observed in PCOS women (9,11,37). However, for the mother to provide a potential source of androgen excess to the fetus, the placental androgenmetabolizing capacity has to be exceeded.…”
Section: Figurementioning
confidence: 94%
“…Different animal models have demonstrated that experimentally induced prenatal androgen excess in female fetuses results in changes that, in adulthood, resemble those observed in PCOS women (9,11,37). However, for the mother to provide a potential source of androgen excess to the fetus, the placental androgenmetabolizing capacity has to be exceeded.…”
Section: Figurementioning
confidence: 94%
“…Exposure to androgen excess can induce a permanent PCOS-like phenotype in adult female mammals [2,3]. Evidence has emerged that ovarian hyperandrogenism can disrupt follicle growth [4].…”
Section: Introductionmentioning
confidence: 99%
“…Exposure to excess androgens during fetal or prepubertal life may induce alterations in the ovary, such as polycystic ovary syndrome (Xita and Tsatsoulis, 2006), increased follicular recruitment (Steckler et al, 2005), and follicular persistence (Manikkam et al, 2006). Sotomayor-Zárate et al (2011) found that exposure to TP at a dose of 1 mg to female rats during the first 12 h of life reduced the number of ovarian follicles, increased cystic follicles, and produced absence of corpora lutea.…”
mentioning
confidence: 97%